Frequency and Risk Factors Associated with Musculoskeletal Pain among the Medical Students of Rawalpindi - Hisam, Aliya; Mashhadi, Syed Fawad; Raja, Amna Kaneez Fatima; Hamza, Muhammad Ameer; Sabir, Rida; Naveed, Tahoora; Umer, Muhammad (Pakistan Armed Forces Medical Journal, 2024)
Objective: To find the frequency and risk factors associated with musculoskeletal pain (MSP) among the medical students of Rawalpindi. Study Design: Analytical cross-sectional study Place and Duration of Study: Army Medical College students, Rawalpindi Pakistan, were enrolled from Mar 2022 to Jul 2022. Methodology: An online, self-administered, altered version of the standardized Nordic Questionnaire was distributed among the students of Army Medical College, Foundation Medical University and Rawalpindi Medical University. Data were analyzed using IBM SPSS-25. Frequencies and means were calculated. Chi-square test and student’s t test were done to find any significant associations with p-value <0.05 taken as statistically significant. Results: The study population consisted of 371 medical students of which 127(34.2%) were males and 244(65.8%) were females. Musculoskeletal pain prevalence reported in the last week was significantly higher in students of clinical years (p=0.008), those with history of trauma (p=0.005), family history of musculoskeletal pain (p<0.001) and those with a higher screen time (p=0.007). Similarly, musculoskeletal pain prevalence reported in the last year was significantly higher in students of clinical years (p=0.003), those with a history of trauma (p=0.004), family history of musculoskeletal pain (p=0.011) and those with higher screen time (p=0.017). Coffee consumption, hours of study and body mass index had no significant association with musculoskeletal pain prevalence. Conclusion: Musculoskeletal pain prevalence proved to be significantly high among the medical students of Rawalpindi.Awareness needs to be spread about this highly prevalent problem with medical colleges taking steps to reduce the contributing factors.